An approach to CLIL teacher language awareness using the Language Triptychh - Martín del Pozo, María Ángeles (Pulso. Revista de educación, 2016)
CLIL teacher training is one of the main challenging concerns of both CLIL theorists and practitioners. This paper aims to contribute to the field by providing an example of a needs analysis for CLIL teacher training regarding linguistic requirements of teaching content subjects through English. The theoretical framework underlying this proposal is the Language Triptych (Coyle et al., 2010) and the dichotomy BICS/CALP (Cummins, 1984). Open questionnaires were administered to six teachers involved in a bilingual degree at Universidad de Valladolid. Data were also gathered from informal interviews. The references to linguistic issues present in their responses are classified according to the three elements of the Language Triptych (language of /for/ through learning) or the BICS/CALP distinction. Teachers show some basic language awareness which can be perceived in their reflections. The paper concludes with a proposal of linguistic contents which, according to the data analysed, seem to be appropriate for language upskilling of those who are considering commencing CLIL.
Keywords: Higher Education; Teacher Training; Laguage Awareness